Police perceptions of their external legitimacy in high and low crime areas of the community - Nix, Justin (Crime & delinquency, 2017)
Until recently, police legitimacy research has primarily focused on citizen perceptions of the police. However, it may be that the police believe citizens associate other factors, such as distributive justice or performance, with legitimacy. The present study adds to the literature by surveying a nationally representative sample of U.S. police officers about how they believe citizens residing in high and low crime areas of the community evaluate police in terms of legitimacy. Findings suggest that respondents believe procedural justice and distributive justice are important to citizens of both areas in terms of generating trust. At the same time, respondents believe that citizens of high and low crime areas feel obligated to obey the police for different reasons.